Pemetaan Kawasan Penelitian Pendidikan Agama Islam Program Pascasarjana IAIN Samarinda - Ahmad Riyadi; Siti Maulidah; Muhammad Nur (Jurnal Tarbiyah dan Ilmu Keguruan Borneo, 2020)
This study originated from the study of Islamic Education in the Samarinda States Islamic Institute’s Postgraduate Program. It has been carried out since the establishment of the Master Program in the concentration of Islamic Education, and has produced many works in the from on Thesis. Thesis is a work which is recognized by its scholarship, is a representation of studies from the field of knowledge. Especially for the Thesis in the field of Islamic Education, until 2017 and has been inventory and entered the library database of Samarinda State Islamic Institute, as many as 70 thesis. From the survey data above, there are several studies in the field of Islamic Religious Education that are still general in nature, not yet able to provide an in-depth overview of Islamic education studies. In the absence of sufficient sources to provide information on the study of Islamic Education in the Samarinda State Islamic Institute Graduated Program, it is not impossible that the same research will occur on a subject that has been carried out by someone else. While from the other side, the research domain or focus in the field of science can provide information and an overview of the direction of Islamic Education studies and their relationship with other disciplines. Therefore, it is necessary to conduct further studies and research on how to map the study of Islamic Education in Samarinda State Islamic Education in the Samarinda State Islamic Institute’s Postgraduate Program. This type of research is a mixed research. The approach in this multidisciplinary by using bibliometric analysis.